تصميم واختبار كفاءة نموذجين لحافظات يمكن أن تستخدم لحفظ البندورة - علي, علي محمد; صافي, زهر (Latakia University Journal -Biological Sciences Series, 2014)
يهدف البحث إلى دراسة نظام التبريد التبخيري في عملية التبريد باستخدام نموذجين من الأوعية (الفخارية، المعدنية). أجريت الدراسة في موقع من محافظة طرطوس في فترة الشهر (الرابع –الخامس –السادس)، لعام 2013، وذلك على ثمار البندورة، فبينت الدراسة أن الفخار يسبب انخفاض في درجة الحرارة بين( 4-6 ) درجة مئوية، وأن المعدن يسبب انخفاض بدرجة الحرارة تتراوح بين (3-5) درجة مئوية، وأن ثمار البندورة المحفوظة بالأوعية الفخارية لم يطرأ عليها أي تلف بنسيجها أو بنيتها خلال مدة الحفظ (27 يوم) مقارنة بالشاهد الذي تعرض للتلف خلال (12 يوم). The research aims to optimize the investment in solar cooling process using two models of vessels (clay- mineral).The study was conducted at the site of Tartous in the month (the fourth - fifth - sixth) years (2013) and that the fruits of the tomato study, she stated that the pottery is causing a drop in temperature between )4-6( degrees Celsius, and that the metal causes the low temperature range between (3-5 ) degrees Celsius although the fruits of tomatoes preserved pottery vessels have not undergone any damage of its structure or texture during the period of conservation (27 days) compared to the control which is exposed to damage during the (12 days).